Mental health and psychosocial support in the face of Ebola in Liberia. Issue 1 (March 2015) - Cooper, Janice L.
<x xml:space="preserve">Abstract</x> This personal reflection is based on the author's experiences, a native Liberian, in her country at the beginning of the 2014 Ebola epidemic. It includes her account of events as Ebola cases and related deaths began to rise and the response appeared inadequate. Examples are presented where a robust psychosocial and mental health response was critically required, but most often lacking. This reflection focuses on the points where the author's personal and the professional life met as she co-led the psychosocial pillar of the national response team on Ebola. It also explores the challenges of leading the mental health and psychosocial component of a complex emergency within a fragile, post conflict state, where the medical and infectious disease component of the response often takes precedence. Additionally, the author's internal struggle that occurred when she was forced to evacuate at the outbreak's peak is explored.